The Representation of Anti-Feminism on TikTok: An Analysis of @suarawanita Content and Its Resonance with Javanese Gender Culture - Ahsin Darojat (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to analyze how the TikTok account @suarawanita represents anti-feminist narrative through translated Western content, how anti-feminist ideology resonates with Javanese gender culture, and how the discourse on career women and domestic women is framed in the content presented. This study uses a qualitative approach with a representation analysis method based on Stuart Hall’s Representation Theory. Data was collected through documentation of videos and comment columns on TikTok account @suarawanita. The result of the study show that the account selectively frames feminism as a threat to family harmony, a source of unhappiness for women, and a cause of damage to gender relations. This narrative resonates with traditional Javanese cultural values that emphasize family harmony, women’s domestic roles, and male leadership. From the perspective of Muslim feminism as advocated by Alimatul Qibtiyah, this representation tends to ignore moderate and progressive approaches that emphasize equality based on justice and shared responbility. This study confirms that the anti-feminist content on the TikTok account @suarawanita not only represents Western feminist ideology, but also creates new meanings that reinforce patriarchy in the context of traditional local Indonesian culture.